The study of services quality by Rapid Kuantan bus - Noordiana, Baharom (2014)
Public transportati011 services play an important role in the country and are seen as a solution to overcome the serious traffic congestion. Traffic congestion caused by the increasing number of private cars and was due to public transport cannot meet the needs and customer satisfaction. Therefore the objective of this study was to determine the level of service quality by Rapid Kuantan Bus and to investigate the factors of strength and weakness by Rapid Kuantan Bus.This study was conducted to find out the respondents' views on the availability of information, comfort, safety and convenience. This study focuses on the quality of service with Rapid Kuantan Bus by using the questionnaire survey method. The study was conducted on 300 respondents randomly involving route 100 Hentian Bandar - Gambang Resort. The results revealed that most respondents said the service quality by Rapid Kuantan Bus was still in good level, especially in term of safety, air condition and physical appearance. Nevertheless, Rapid Kuantan Bus should improve their service quality in seat availability, crowdedness and exchange money for price fare. Recommendations have been made based on the results of the study is to provide two different types of buses, provides free Wi-Fi and provides ticketing system.